AMOSTRAGEM DE FOLHA EM CANA-DE-AÇÚCAR SUBMETIDA À ADUBAÇÃO NITROGENADA - Rozane, Danilo Eduardo; Prado, Renato de Mello; Romualdo, Liliane Maria; Pancelli, Márcio Alexandre; Franco, Claudenir Facincani (REVISTA DE AGRICULTURA, 2015)
AMOSTRAGEM DE FOLHA EM CANA-DE-AÇÚCAR SUBMETIDA À ADUBAÇÃO NITROGENADA